2022
DOI: 10.3390/ijms231911617
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Analysis of Chloroplast Genomes in Five Uncaria Species Endemic to China

Abstract: Uncaria, a perennial vine from the Rubiaceae family, is a typical Chinese traditional medicine. Currently, uncertainty exists over the Uncaria genus’ evolutionary relationships and germplasm identification. The complete chloroplast genomes of four Uncaria species mentioned in the Chinese Pharmacopoeia and Uncaria scandens (an easily confused counterfeit) were sequenced and annotated. The findings demonstrated that the whole chloroplast genome of Uncaria genus is 153,780–155,138 bp in full length, encoding a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 105 publications
5
15
0
Order By: Relevance
“…2). Similar to the previous results for other study, most of the codons ending with A or T have RSCU values greater than 1, while, most of those ending with C or G have RSCU values of less than 1 [21][22][23].…”
Section: Characteristics Of P Cistena Cp Genomessupporting
confidence: 90%
“…2). Similar to the previous results for other study, most of the codons ending with A or T have RSCU values greater than 1, while, most of those ending with C or G have RSCU values of less than 1 [21][22][23].…”
Section: Characteristics Of P Cistena Cp Genomessupporting
confidence: 90%
“…Thus, we can assure that the difference among their chloroplast genomes is in their intergenic regions. However, for other Uncaria species, it has been previously reported a variation in the number of genes, with U. scandens presenting the lowest number of genes (128) within the genus so far 41 . From the comparative analysis among the species of this subfamily, we found an evolutionary conservation of these genomes’ quadripartite structure: a LSC, a SSC and two IRs regions.…”
Section: Discussionmentioning
confidence: 93%
“…Closely related species tend to have similar genomic characteristics and the difference in the size of the LSC, SSC and IR regions among the species can only explain 20% of the variation on cpDNA size 44 , 45 . Within Cinchonoideae, U. tomentosa was the species with the longest cpDNA sequence, 156,390 bp, even when compared to other asian Uncaria species 41 , while U. rhynchophylla showed the shortest, 154,605 bp, but U. scandens has the shortest cpDNA for the genus so far (153,780 bp)41 . We found that the difference in genome size can be related to non-coding sequences.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Codon preferences are in uenced by natural selection, base mutations, and genetic drift, are the result of long-term evolution of species in response to environmental selection, and affect the expression of mRNA and protein levels in the genome [46][47][48][49][50] . The most abundant amino acid in both species is leucine (Leu), with an average of 2,279, which is also common in other angiosperm species 51,52 . Meanwhile, based on the results of other angiosperm cp genomes, our study demonstrated that most codons ending in A/U have RSCU values higher than 1, which may be caused by a composition bias towards high A/T ratios 53,54 .…”
Section: Repeat Sequence and Codon Bias Analysismentioning
confidence: 99%